Biomimetic Glycopolypeptide Hydrogels with Tunable Adhesion and Microporous Structure for Fast Hemostasis and Highly Efficient Wound Healing. (2nd August 2021) - Teng, Lin; Shao, Zhengwei; Bai, Qian; Zhang, Xueliang; He, Yu‐Shi; Lu, Jiayu; Zou, Derong; Feng, Chuanliang; Dong, Chang‐Ming
Abstract: Despite clinical applications of the first‐generation tissue adhesives and hemostats, the correlation among microstructure and hemostasis of hydrogels with wound healing is less understood and it is elusive to design high‐performance hydrogels to meet worldwide growing demands in wound closure, hemostasis, and healing. Inspired by the microstructure of extracellular matrix and mussel‐mimetic chemistry, two kinds of coordinated and covalent glycopolypeptide hydrogels are fabricated, which present tunable tissue adhesion strength (14.6–83.9 kPa) and microporous structure (8–18 µm), and lower hemolysis <1.5%. Remarkably, the microporous size mainly controls the hemostasis, and those hydrogels with larger pores of 16–18 µm achieve the fastest hemostasis of ≈14 s and the lowest blood loss of ≈6% than fibrin glue and others. Moreover, both biocompatibility and hemostasis affect wound healing performance, as assessed by hemolysis, cytotoxicity, subcutaneous implantation, and hemostasis and healing assays. Importantly, the glycopolypeptide hydrogel‐treated rat‐skin defect model achieves full wound closure and regenerates thick dermis and epidermis with some hair follicles on day 14. Consequently, this work not only establishes a versatile method for constructing glycopolypeptide hydrogels with tunable adhesion and microporous structure, fast hemostasis, and superior healing functions, but also discloses a useful rationale for designing high‐performance hemostatic and healing hydrogels. Abstract : Two kinds of coordinated and covalent glycopolypeptide hydrogels are fabricated, which present tunable tissue adhesion strength, microporous structure, and lower hemolysis. The large microporous hydrogels achieve superior hemostasis and regenerate thick dermis/epidermis with some hair follicles during wound healing. Significantly, this work discloses the correlation of microstructure‐hemostasis‐wound healing, guiding the design of high‐performance hydrogels‐based hemostatic and healing adhesives and dressings.